Developing a Stakeholder Approach for Recruiting Top-Level Sales Students. (April 2014) - Agnihotri, Raj; Bonney, Leff; Dixon, Andrea Leigh; Erffmeyer, Robert; Pullins, Ellen Bolman; Sojka, Jane Z.; West, Vicki
With growing industry demand for sales professionals, recruitment at colleges and universities that have a sales education focus has increased remarkably over the past few years. However, results indicate that hiring organizations face an uphill task in filling sales positions. Recruiters and students struggle to build critical person–job fit during a relatively brief period of interaction. To address these issues, the present article presents a two-staged ideal recruitment process based on a stakeholder perspective. A set of 16 propositions is provided for improving key outcomes of the sales student recruitment process.